Social Rights Enforcement: Some Contributions from Legal Theory - Pacheco Rodríguez, Miguel Ángel (2017)
This paper explores some of the main contributions developed bylegal theory in favour of social rights enforcement. The first part is devotedto the concept of subjective right and particularly to the conceptions due toRobert Alexy and Luigi Ferrajoli. The second part includes the analysis ofthe relationship between social rights and the principle of equality. Specialattention will be given to Luis Prieto’s theory. Finally, both post-positivisticand neo-constitutionalistic theories of Law will be evaluated in terms of theirdegree of recognition and defence of social rights.